Extraction and Identification of Some Antioxidant and Antimicrobial Compounds from Urena Lobata (Linn) Leaves - Adeloye, Adewale Olufunsho (2015)
This study examined the extract of Urena lobata L. leaves for its antioxidant, antibacterial and antifungal activities with a view to isolating and characterizing the biologically active components that might be present and thus provide justification for the ethnomedicinal uses of the plant in the treatment of various diseases for which it was used.